SENIOR SEMINAR: THE SOCIOLOGY OF CHILDHOOD - Thorne, Barrie (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this seminar we will place children, and varied contexts of growing up, at the center of inquiry. We will open with the idea of childhood as a social and cultural variation, in assumptions about the "nature," needs, and capacities of girls and boys of particular ages. We will also consider multiple, sometimes contested representations of children, and the changing, increasingly commercialized nature of U.S. children’s lives. The next part of the course will focus on the experiences of children who are differently positioned by gender, social class, and racialized ethnicity – their material circumstances, social relations and worlds of meaning; and their relations with adults, including processes of care, control, negotiations of autonomy, and issues of child abuse and children’s rights. The last topic highlights a theme basic to the course: that children are not only affected by adults, but also help shape their own, and adult experiences.